2018
DOI: 10.29309/tpmj/2018.25.06.274
|View full text |Cite
|
Sign up to set email alerts
|

Dengue Fever

Abstract: Objectives: To determine the frequency and characteristics of dengue patients.Study Design: Cross sectional observational study. Setting: Qazi Hussain Ahmed MedicalComplex Nowshera. Period: 5th July to 25th Sept 2017. Material and Methods: A total of72 cases were received for dengue serology. Relevant information’s were collected on a predesignedquestionnaire prepared in accordance with the objectives of the study. Results: Atotal of 117 patients were referred from fever clinic and emergency OPD for dengue ser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…The minimum number of cases (N=38) were reported from KP (Usman et al, 2011) while the maximum number of cases (N=3342) were reported from Sindh during decade I (Khan et al, 2007(Khan et al, , 2008Hasan et al, 2013, Ahmed et al, 2008Riaz et al, 2009;Shamim, 2010;Wasay et al, 2008a, b;Khalil et al, 2014;Baqi et al, 2010;Ali et al, 2011;Jahan et al, 2011). Of all the cases from KP, high number of cases (N=22740) were reported from district Swat during 2013 which are 48.6% of the total dengue cases reported from the province (Ali et al, 2016;Khan and Khan, 2015;Chaudhry et al, 2017;Lutfullah et al, 2017;Suleman et al, 2016;Khan et al, 2017a;Khan, 2018;Khan and Bari, 2018). Similarly, 58.5% (4475/7649) of the total cases reported from Punjab were from the capital city Lahore only during 2011 (Iqtadar et al, 2017b;Khan et al, 2013a, b;Ahmed et al, 2013;Rashid et al, 2012;Mahmood et al, 2013;Saqib et al, 2014a, b;Asghar and Farooq, 2011;Idrees et al, 2012;Raza et al, 2017;Naeem et al, 2018;Assir et al, 2014a, b;Sheikh et al, 2012;Chaudhry et al, 2018).…”
Section: Province-wise Distributionmentioning
confidence: 99%
“…The minimum number of cases (N=38) were reported from KP (Usman et al, 2011) while the maximum number of cases (N=3342) were reported from Sindh during decade I (Khan et al, 2007(Khan et al, , 2008Hasan et al, 2013, Ahmed et al, 2008Riaz et al, 2009;Shamim, 2010;Wasay et al, 2008a, b;Khalil et al, 2014;Baqi et al, 2010;Ali et al, 2011;Jahan et al, 2011). Of all the cases from KP, high number of cases (N=22740) were reported from district Swat during 2013 which are 48.6% of the total dengue cases reported from the province (Ali et al, 2016;Khan and Khan, 2015;Chaudhry et al, 2017;Lutfullah et al, 2017;Suleman et al, 2016;Khan et al, 2017a;Khan, 2018;Khan and Bari, 2018). Similarly, 58.5% (4475/7649) of the total cases reported from Punjab were from the capital city Lahore only during 2011 (Iqtadar et al, 2017b;Khan et al, 2013a, b;Ahmed et al, 2013;Rashid et al, 2012;Mahmood et al, 2013;Saqib et al, 2014a, b;Asghar and Farooq, 2011;Idrees et al, 2012;Raza et al, 2017;Naeem et al, 2018;Assir et al, 2014a, b;Sheikh et al, 2012;Chaudhry et al, 2018).…”
Section: Province-wise Distributionmentioning
confidence: 99%